Analyzing Higher and Lower Order Thinking Skills in the “English for Nusantara” Grade VIII Textbook Reading Comprehension Exercises - Puspitaloka, Nina; Ermanto, Ermanto; Zainil, Yetti (JOLLT Journal of Languages and Language Teaching, 2026)
Textbooks serve an important impact in molding students' learning outcomes, especially in terms of reading comprehension and cognitive skills. Recent research on Indonesian EFL textbooks, however, indicates that comprehension tasks are frequently dominated by lower level thinking skills (LOTS), with few possibilities for higher order thinking skills (HOTS). The purpose of this study is to determine the extent to which LOTS and HOTS are reflected in the reading comprehension activities of the English for Nusantara textbook. A qualitative content analysis approach was used to assess 64 reading comprehension questions from five chapters using Bloom's Revised Taxonomy. The data suggest that LOTS are more prominently represented (64%), particularly at the remembering and comprehending levels, while HOTS appear to a lesser extent (36%) while analyzing and assessing activities. The generating level (C6) was missing from all chapters. Although the cognitive requirement gradually increased in later chapters, the overall distribution remained imbalanced, with LOTS dominating the majority of activities. Beyond description, these findings have practical ramifications. Teachers are encouraged to enhance their classroom practice by including HOTS-oriented activities such as debates, project-based learning, and creative writing projects to build evaluation and creation abilities. Textbook authors and curriculum developers, meanwhile, should redesign future editions to include a more balanced number of LOTS and HOTS, ensuring that comprehension exercises not only strengthen core literacy but also challenge students to think critically and creatively. By doing so, textbooks can better connect with the ideals of the Kurikulum Merdeka and the Profil Pelajar Pancasila.